Macrotristria monteithi sp. n., a large new cicada from central Queensland with a small distribution (Cicadoidea, Cicadidae, Macrotristriini) - Moulds, M.s. (Zootaxa, 2022)
A new species of cicada, Macrotristria monteithi sp. n., is described from the southern Carnarvon and Expedition Ranges in central Queensland, Australia. It is a large species allied to the common and widespread species M. angularis, but unlike that species it has a comparatively narrow distribution.